IMPLEMENTASI PROGRAM PARKIR ELEKTRONIK (E-PARKING) DALAM PENGELOLAAN PARKIR DI KOTA SEMARANG (STUDI KASUS DI JALAN DEPOK) - Alzena, Calista Putri Widna; Marom, Aufarul; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2024)
Implementation of the e-parking program on Jalan Depok, Semarang City faces several challenges. This starts with the large number of private vehicles which affects the parking sector. Depok Road itself was also affected because this road is a trade road and is crossed by 3 golden roads. Apart from that, illegal parking lots that do not officially deposit fees are also an obstacle in optimizing parking fee revenues. This research aims to look at the implementation of the eparking program on Jalan Depok, Semarang City and also the factors that influence the program implementation process. This research method is descriptive qualitative with data collection techniques through interviews, documentation and observation. The sampling technique is purposive sampling and data validity through source triangulation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. The results of this research were analyzed through organization, interpretation, and application based on Jones' theory. Fulfillment of organizational aspects such as standards and procedures needs to be optimized. Interpretation of the program is still limited in the community, even though there has been socialization. In the application, parking levy income has increased, but has not yet reached the PAD target. Supporting factors include adequate budget resources, while inhibiting factors involve a lack of public outreach and understanding, as well as obstacles in the bureaucratic structure. The recommendations of this research are the expansion and consistency of socialization through face-to-face meetings and social media, coaching for jukirs, regular training to increase understanding, and updating regulations and SOPs. Periodic evaluation is needed to improve program effectiveness.